2021
DOI: 10.3389/fmicb.2021.643045
|View full text |Cite
|
Sign up to set email alerts
|

The Subcellular Proteome of a Planctomycetes Bacterium Shows That Newly Evolved Proteins Have Distinct Fractionation Patterns

Abstract: The Planctomycetes bacteria have unique cell architectures with heavily invaginated membranes as confirmed by three-dimensional models reconstructed from FIB-SEM images of Tuwongella immobilis and Gemmata obscuriglobus. The subcellular proteome of T. immobilis was examined by differential solubilization followed by LC-MS/MS analysis, which identified 1569 proteins in total. The Tris-soluble fraction contained mostly cytoplasmic proteins, while inner and outer membrane proteins were found in the Triton X-100 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It has been previously observed that Planctomycetota is the phylum containing the aquatic MAG with the biggest known estimated genome size (14.93 Mbp) [ 2 ]. These large genomes contain large collections of genes that could be linked to the very complex cell structures and chromosomes observed in this phylum [ 36 ]. Still, further research is necessary to understand if extant genome size in phylum Plactomycetota is the result of ecological adaptation to abiotic gradients.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously observed that Planctomycetota is the phylum containing the aquatic MAG with the biggest known estimated genome size (14.93 Mbp) [ 2 ]. These large genomes contain large collections of genes that could be linked to the very complex cell structures and chromosomes observed in this phylum [ 36 ]. Still, further research is necessary to understand if extant genome size in phylum Plactomycetota is the result of ecological adaptation to abiotic gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Biological triplicates of fractions DGUC F3 and F6 from A. kunkeei strains A1401 and A0901 were subjected for proteomics analysis after in-solution digestion, essentially as described previously (Seeger et al 2021 ). Notably, for the F6 samples that contained a high concentration of proteins, 10 μg of proteins was used for the digestion (ca 10 μl of the sample).…”
Section: Methodsmentioning
confidence: 99%
“…Extracted proteins of the WCL and CFP fractions were analyzed by Label-free quantification (LFQ) by LC-MS/MS as described previously (Seeger et al 2021 ). For the LFQ analyses, MS raw files were processed using MaxQuant software (Cox and Mann 2008 ) and the Andromeda search engine (Cox et al 2011 ) against the genome sequences of A. kunkeei A0901 and A1401.…”
Section: Methodsmentioning
confidence: 99%
“…Even though bacterial cells generally do not contain internal compartments, there are exceptions, like bacteria of the Planctomycetes phylum that contain a proteinaceous cell wall and an invaginated inner membrane (Mahajan et al 2020 ). In Tuwongella immobilis , Siv and her team visualised a complex tunnel system made by the invaginations thus resulting in an increased periplasmic space (Seeger et al 2021 ). While the function of this extended compartment is not fully understood yet, it is hypothesised that the bacterium uses the periplasm for storage and degradation of imported macromolecules.…”
Section: Compartmentalizing Tasks and Functionsmentioning
confidence: 99%